2018
DOI: 10.1140/epjc/s10052-018-5912-z
|View full text |Cite
|
Sign up to set email alerts
|

Heavy quarkonia in a potential model: binding energy, decay width, and survival probability

Abstract: Recently a lot of progress has been made in deriving the heavy quark potential within a QCD medium. In this article we have considered heavy quarkonium in a hot quark gluon plasma phase.The heavy-quark potential has been modeled properly for short as well as long distances. The potential at long distances is modeled as a QCD string which is screened at the same scale as the Coloumb field. We have numerically solved the 1+1-dimensional Schrodinger equation for this potential and obtained the eigen wavefunction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…As a general remark, we note that the obtained spectrum is similar to the results of nonrelativistic and semirelativistic calculations [43][44][45][46][47][48][49][50][51][52][53][54][55][56]. In this concern, it can be argued that the high value of the bottom quark mass tends to reduce the relativistic effects with respect, for example, to the charmonium case.…”
Section: Bottomonium Spectrumsupporting
confidence: 78%
“…As a general remark, we note that the obtained spectrum is similar to the results of nonrelativistic and semirelativistic calculations [43][44][45][46][47][48][49][50][51][52][53][54][55][56]. In this concern, it can be argued that the high value of the bottom quark mass tends to reduce the relativistic effects with respect, for example, to the charmonium case.…”
Section: Bottomonium Spectrumsupporting
confidence: 78%
“…So far no attempts to solve quarkonium potential using SUSYQM was reported Refs. [4][5][6][7][8][9][10][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the present of 1S state of bottomonium is an agreement with Refs. [54,55], in which the calculations are achieved in hot medium only.…”
Section: In Fig (4) the Binding Energy Of 1s State Of Bottomonium Is ...mentioning
confidence: 99%
“…In Refs. [6,29,31] , the authors found that the bottomonium melts above the critical temperature. In Ref.…”
Section: Discussion Of Resultsmentioning
confidence: 99%